PENGARUH BAURAN PEMASARAN DAN KUALITAS PELAYANAN TERHADAP MINAT BERKUNJUNG KEMBALI DI HEHA SKY VIEW GUNUNG KIDUL YOGYAKARTA - Winarni, Selo; Adhiyani, Oryza Rully (PRIMA EKONOMIKA, 2023)
As one of tourism object, Heha Sky View has many efforts to increase revisiting domestic or international tourists. This research aim to observe the impact of marketing mix and service quality on interest in revisiting to Heha Sky View Tourism in Gunung Kidul, Special Region of Yogyakarta partially or simultaneously.The type of research was a survey research, with a quantitative descriptive approach. Population in this study were respondents who had visited the Heha Sky View Tour of Gunung Kidul, Special Region of Yogyakarta. As much as 70 respondents taken as sample. Data resources include primary data obtained by giving questionnaires directly and secondary data include literature study and documentation. The analysis includes classical assumption test , Multiple Linear Regression, Hypothesis Testing using t Test, F Test and Coefficient of Determination Test. Data processing was carried out using SPSS computer software version 23.The results showed that the marketing mix variable (X1) and service quality (X2) has positive impact to interest in revisiting partially which significant value was 0.000 <0.05. The marketing mix variables and service quality have a significant effect on the interest in revisiting simultaneously which significant value is 0.000 <0.05. and F count is greater than F table (3.13) In addition, the results of the calculation of Adjusted R Square marketing mix and service quality contribute 0.687 or 68.7% to the interest in revisiting. While the remaining 31.3% is influenced by other models in this study. Keywords: Marketing Mix, Service Quality, Interest in Revisiting.